Nature Experiences of Older People for Active Ageing: An Interdisciplinary Approach to the Co-Design of Community Gardens - Boffi, Marco; Pola, Linda; Fumagalli, Natalia; Fermani, Elisabetta; Senes, Giulio; Inghilleri, Paolo (Frontiers in Psychology, 2021)
Two relevant phenomena are taking place in Western countries: the amount of people living in urban areas is increasing, and the population is aging. In this context the concept of active aging, that is favoring health, participation, and security to increase the quality of life of the elders, has become a key issue. Hence, effectively designing public green spaces in urban areas is crucial to promote active aging, as they can encourage social relations and the interaction with natural healthy contexts. Consistently with such perspective, existing landscape design criteria point out the importance of considering not only functional and aesthetic elements but also the ecosystemic and biophilic relation between people and environment, producing positive effects for both. To maximize the impact of such design criteria, proper engagement strategies are desirable, both to assign an active role to elders and to inform the fine tuning of the design process according to specific needs of local population. The current study presents an interdisciplinary co-design method that allows to inform a biophilic approach by describing the experience of people in natural environments, actual and designed, through the factors of the Attention Restoration Theory (ART). The case study is developed through six focus groups with elders for the co-design of a restorative area in a community garden in the Ortica district in Milan (Italy). Results show how the main needs expressed by participants regard the ART factors “compatibility” (a multifunctional garden), “fascination” (sense of contact with nature) and “being away” (metaphoric escape from nursing homes). The garden designed including biophilic principles answers such needs, and specific links with designed elements are identified. For example, “Being away” (e.g. isolation from daily routine, visual occlusion of the surroundings) and “compatibility” (e.g. pergola, aesthetic value) are the factors that include the elements more satisfactorily answering previous needs. “Fascination” also includes many positive aspects, letting space for improvement (e.g. more water elements, interaction with animals). Implications of the method are discussed, regarding the importance of subjective experience to inform design, the use of different psychological constructs to describe it, and the methodological alternatives for the psychological assessment.